Research on Elastic Characteristics of Negative Pressure Rubber Isolator - Wang, Jianwei; Feng, Jinlong (Manufacturing Technology Journal, 2023)
Aiming at obtaining ultra-low kinematic stiffness and improving the isolation property of low frequency vibration, it is necessary to solve the coupling parameters and rated load of air negative pressure characteristics and rubber characteristics, in order to achieve an ideal elastic characteristic curve of air negative pressure spring. Firstly, the background and working principle of the negative pressure rubber isolation were introduced. In addition, the FEA model of isolator is built based on Mooney-Rivlin constitutive model of rubber. Furthermore, to testify the validity of the mathematical model, the static characteristic and simulation analysis of isolator are studied. The experimental data and characteristic curve of different negative pressure were obtained, the simulated results show a good agreement with those of corresponding experiments. Finally, they also illustrate the validity of the vibration isolation, which realizes better performance of low-frequency vibration isolation.
Keywords: Vibration Isolation; Low-frequency; Constitutive Model; Elastic Characteristics